Wetlands as a Tool for Water Treatment - Jay Capasso; Lisa Krimsky; Jehangir Bhadha (EDIS)
Wetlands are often referred to as "nature's kidneys" because of their ability to remove pollutants from water via storage in the soil and vegetation, as well as through losses to the atmosphere. This 7-page fact sheet written by Jay Capasso, Lisa Krimsky, and Jehangir Bhadha and published by the UF/IFAS School of Forest Resources and Conservation provides a general overview of the function and structure of large-scale treatment wetlands and the services they provide. http://edis.ifas.ufl.edu/fr419